Histoire du Trade unionisme. - Webb, Sidney; Webb, Beatrice (Paris : Giard & Brière, 1897)
Vrijzinnige werkmansbibliotheek
Frans
Monografie
Keywords: socialistische arbeidersbeweging; vakbonden; Groot-Brittannië.